Multidisciplinary Approach to Rehabilitation after Tumor Resective Jaw Surgery: A 9-Year Follow-Up - Igor Smojver; Marko Vuletić; Spomenka Manojlović; Dragana Gabrić (Hindawi Limited, 2020)
A 36-year-old male patient presented at the Department of Maxillofacial Surgery, University Hospital Clinic Zagreb in December 2010 due to a swelling of the left body of the mandible that was noticed 4 months earlier. The patient was referred regarding an atypical clinical and radiological finding in the form of a multicystic appearance in the corpus of the left mandible and teeth mobility in the same region. A probatory biopsy was performed under local anesthesia and sent for histopathologic examination which reported odontogenic myxoma. The tumor was removed with a marginal resection of the mandible from the left first incisor to the left second molar. Two years after surgery, in January 2013, the patient was referred to the oral surgeons for implant-prosthodontic rehabilitation. Two narrow implants were placed at positions 32 and 36, and three months afterwards, implant-retained denture was made using locator connections to compensate lost teeth and to correct the ratio of soft tissues and facial contours. The patient was followed-up for 9 years without any functional and aesthetic problems. Loosing function and aesthetic morbidity, after radical surgical treatment, often have compromised the quality of life of this group of patients. It is important to highlight the need for multidisciplinary collaboration for the complete rehabilitation of the patient after surgical oncology of the maxillofacial region.